MO812THE COMPARISON OF HIGH-DOSE HAEMODIAFILTRATION WITH HIGH-FLUX HAEMODIALYSIS (CONVINCE) STUDY: BASELINE CHARACTERISTICS AND PROOF OF PRINCIPLE OF THE CONVECTION VOLUME DELIVERED. (29th May 2021) - Vernooij, Robin; Lee, Mei-Man; Woodward, Mark; Hegbrant, Jörgen; Canaud, Bernard; Cromm, Krister; Torok, Marietta; Fischer, Kathrin; Barth, Claudia; Strippoli, Giovanni; Blankestijn, Peter J; Bots, Michiel
Abstract: Background and Aims: Although high-dose haemodiafiltration (HDF) has shown some promising survival advantage compared with high-flux haemodialysis (HD), the evidence remains controversial. In view of these discrepant results, a definitive trial is required to determine whether high-dose HDF is superior to high-flux HD. The comparison of high-dose HDF with high-flux HD (CONVINCE) study will assess the benefits and harms of high-dose HDF versus conventional high-flux HD in adults with end-stage kidney disease (ESKD). Here we provide information on the baseline characteristics of the included patients and evaluate whether the patients randomised to HDF were able to reach a high-dose convection volume. Method: This international, prospective, open label, randomised, controlled trial is aiming to recruit 1800 ESKD adults treated with high-flux HD in 9 European countries. Patients will be randomised 1:1 to high-dose HDF versus continuation of conventional high-flux HD. High-dose HDF is defined as a convection volume per session of ≥23 L (range ±1 L). The trial is designed with a follow-up time for each patient of at least 24 months and will assess all-cause mortality, cause-specific mortality, cardiovascular events, hospitalisation, patient-reported outcomes, and cost-effectiveness. For this study we tabulated the baseline characteristics for all randomised participants by treatment groups. For the patients randomised to HDF, we calculated the proportion of the patients reaching a convection volume of ≥ 23L. session on the first visit after baseline (i.e. 3 months) and compared baseline and treatment characteristics with the patients with a convection volume of <23L/session. Results: CONVINCE has recruited, until the start of January 2021, 1139 patients in eight European countries. The mean age was 62.4 (SD: 13.2) years and 62% (n=709) patients were men. The mean dialysis vintage was 5.0 (6.1) years. The mean systolic blood pressure (BP) was 141 (22) mmHg, the diastolic BP was 73 (14) mmHg, and the body mass index (BMI) was 27.6 (5.7) kg/m2. Approximately one-third the patients had diabetes mellitus and 21% had a history of coronary heart disease at baseline. Of the patients randomised to HDF, over 85% achieved a convection volume of ≥23L/session. There were no apparent differences in baseline and treatment characteristics between the patients who reached a convective volume of ≥23L/session versus those who did not: the vascular access was, respectively, a fistula (82% vs 81%), catheter (13% vs 14%), and graft (5% vs 5%) access. Conclusion: The CONVINCE study will run up to 2023 and addresses the question of benefits and harms, regarding survival, hospitalisation, patient-reported outcomes, and cost-effectiveness of high-dose HDF compared with high-flux HD in patients with ESKD. This first analysis shows that achievement of high-dose HDF is feasible for most patients and, most importantly, could be maintained during the present trial period.